12 women in sports - Ventura, Marne (Women who changed the world (12 Story Library (Firm)), 2020)
Showcases twelve female pioneers in sports. Briefly describes their lives and work and spotlights facts about their careers. Short essays at the end of the book highlight female athletes who are relatively unknown. Includes a glossary, resources for further reading, and an index.